2019
DOI: 10.1016/j.jpeds.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Steroid Exposure, Aerobic Fitness, and Physical Activity in Adolescents Born Preterm with Very Low Birth Weight

Abstract: Objective To determine whether antenatal corticosteroid exposure is associated with aerobic fitness or physical activity participation in adolescents born preterm with very low birth weight (VLBW). Study design Observational cohort study of 14-year-old adolescents (n = 173) born with VLBW between 1992 and 1996 at a regional perinatal center with 91 exposed to antenatal corticosteroids. Aerobic fitness was determined from peak oxygen uptake (_ VO 2 peak) obtained via maximal exercise testing on a cycle ergomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…To allow this approach, antenatal steroids are common practice. Nixon et al 1 studied whether antenatal corticosteroid exposure is associated with aerobic fitness or physical activity participation in adolescents born preterm with very low birth weight (VLBW). They found that exposure to antenatal corticosteroids was associated with greater physical activity participation and aerobic fitness, particularly in nonblack male adolescents.…”
Section: Neonatal Lung Diseasesmentioning
confidence: 99%
“…To allow this approach, antenatal steroids are common practice. Nixon et al 1 studied whether antenatal corticosteroid exposure is associated with aerobic fitness or physical activity participation in adolescents born preterm with very low birth weight (VLBW). They found that exposure to antenatal corticosteroids was associated with greater physical activity participation and aerobic fitness, particularly in nonblack male adolescents.…”
Section: Neonatal Lung Diseasesmentioning
confidence: 99%